2000
DOI: 10.2337/diabetes.49.9.1434
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that carotid bodies play an important role in glucoregulation in vivo.

Abstract: The carotid bodies are sensitive to glucose in vitro and can be stimulated to cause hyperglycemia in vivo. The aim of this study was to determine if the carotid bodies are involved in basal glucoregulation or the counterregulatory response to an insulin-induced decrement in arterial glucose in vivo. Dogs were surgically prepared >16 days before the experiment. The carotid bodies and their associated nerves were removed (carotid body resected [CBR]) or left intact (Sham), and infusion and sampling catheters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
135
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(149 citation statements)
references
References 44 publications
11
135
3
Order By: Relevance
“…The glucosesensing role of the CB was suggested by reports that anesthetized animals show a rapid increase in the output of hepatic glucose after infusion of the CB region with sodium cyanide (15,16) or alterations of carbohydrate metabolism in acute hypoxia (17). In addition, it was known that the counterregulatory response to insulininduced mild hypoglycemia (8) or the neurosecretory response in exercise (9) in dogs was impaired after resection of the carotid body and surrounding tissues. It has also been hypothesized that CB dysfunction could be one of the factors underlying type 2 diabetes (18).…”
Section: Research Design/methods and Results-removalmentioning
confidence: 99%
“…The glucosesensing role of the CB was suggested by reports that anesthetized animals show a rapid increase in the output of hepatic glucose after infusion of the CB region with sodium cyanide (15,16) or alterations of carbohydrate metabolism in acute hypoxia (17). In addition, it was known that the counterregulatory response to insulininduced mild hypoglycemia (8) or the neurosecretory response in exercise (9) in dogs was impaired after resection of the carotid body and surrounding tissues. It has also been hypothesized that CB dysfunction could be one of the factors underlying type 2 diabetes (18).…”
Section: Research Design/methods and Results-removalmentioning
confidence: 99%
“…Although not discussed here, there is evidence that glomus cells in the carotid body are also activated by hypoglycemia and may contribute to the overall control of counter-regulation. 59,60 The role of Glut2, glucokinase and the K ATP channel in the control of glucagon secretion has been investigated in several studies. Mice with inactivation of the Glut2 gene, and that express a transgenic glucose transporter in their pancreatic beta-cells to preserve normal glucose-stimulated insulin secretion (ripglut1;glut2 À/À mice), 61 display plasma glucagon levels in the fed state that are abnormally high.…”
Section: S64mentioning
confidence: 99%
“…Hypothalamic glucose sensors are tightly linked with central nervous networks regulating energy homeostasis (14). Additional glucose sensors are localized in the portal vein (25,26) and carotid body (27,28), which via afferent fibers to the hypothalamus and other brain areas can likewise influence eating behavior. It is worth mentioning in this context that in a stepwise hypoglycemic clamp study, we have recently shown that even slightly lowering plasma glucose levels to 4.1 mmol/l in comparison to a level of 5.2 mmol/l increased feelings of hunger in healthy subjects (29).…”
Section: Hormonesmentioning
confidence: 99%